Bioinspired Geometry-Switchable Janus Nanofibers for Eye-Readable H-2 Sensors - Han, Heetak; Baik, Sangyul; Xu, Borui; Seo, Jungmok; Lee, Sanggeun; Shin, Sera; Lee, Jaehong; Koo, Ja Hoon; Mei, Yongfeng; Pang, Changhyun; Lee, Taeyoon (WILEY-V C H VERLAG GMBH, 2017)
Nanoscale architectures found in nature have unique functionalities and their discovery has led to significant advancements in various fields including optics, wetting, and adhesion. The sensilla of arthropods, comprised of unique hierarchical structures, are a representative example which inspired the development of various bioinspired systems, owing to their hypersensitive and ultrafast responsivity to mechanical and chemical stimuli. This report presents a geometry-switchable and highly H-2-reactive Janus nanofiber (H-NF) array inspired by the structural features of the arthropod sensilla. The H-NF array (400 nm diameter, 4 mu m height, 1.2 mu m spacing distance, and hexagonal array) exhibits reversible structural deformation when exposed to a flammable concentration of hydrogen gas (4 vol% H-2 in N-2) with fast response times (5.1 s). The structural change can be detected with the bare eye, which is a result of change in the optical transmittance due to the structural deformation of the H-NF array. Based on these results, an eye-readable H-2-sensor that requires no additional electrical apparatus is demonstrated, including wetting-controllable H-2-selective smart surfaces and H-2-responsive fasteners.
Keywords: HYDROGEN; NANOSTRUCTURES; FILMS